2012
DOI: 10.1007/s00244-012-9823-y
|View full text |Cite
|
Sign up to set email alerts
|

Humic Substances Increase Survival of Freshwater Shrimp Caridina sp. D to Acid Mine Drainage

Abstract: Humic substances (HS) are known to decrease the toxicity of heavy metals to aquatic organisms, and it has been suggested that they can provide buffering protection in low pH conditions. Despite this, little is known about the ability for HS to increase survival to acid mine drainage (AMD). In this study, the ability of HS to increase survival of the freshwater shrimp (Caridina sp. D sensu Page et al. in Biol Lett 1:139-142, 2005) to acid mine drainage was investigated using test waters collected from the Mount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…This is the first study to show that HA significantly decreases ventilation frequency and acute toxicity in fish exposed to AMD. HA have been shown previously to increase survival of shrimp and mayflies to AMD (Holland et al, 2013(Holland et al, , 2014b. This study and results provided in Holland et al (2013Holland et al ( , 2014a, suggest that the presence of HA has a positive effect on aquatic organisms and may aid their survival to multiple stressors such as low pH and heavy metal mixtures associated with AMD.…”
Section: Tablementioning
confidence: 57%
See 4 more Smart Citations
“…This is the first study to show that HA significantly decreases ventilation frequency and acute toxicity in fish exposed to AMD. HA have been shown previously to increase survival of shrimp and mayflies to AMD (Holland et al, 2013(Holland et al, , 2014b. This study and results provided in Holland et al (2013Holland et al ( , 2014a, suggest that the presence of HA has a positive effect on aquatic organisms and may aid their survival to multiple stressors such as low pH and heavy metal mixtures associated with AMD.…”
Section: Tablementioning
confidence: 57%
“…This decreased the amount of pH drift during the trial period. The use of MOPS as a buffer was deemed appropriate as previous studies have shown MOPS to be nontoxic to freshwater species (De Schamphelaere et al, 2004;Rendal et al, 2012;Holland et al, 2013), and pilot trials also showed MOPS to also be non-toxic to the eastern rainbowfish used in this study. The use of MOPS buffer was also deemed appropriate as it has been previously used in a number of studies involving the ecotoxicology of metals in freshwater (De Schamphelaere et al, 2004;Rendal et al, 2012) and has been previously shown to not bind to or influence metal speciation (Kandegedara and Rorabacher, 1999).…”
Section: Methodsmentioning
confidence: 94%
See 3 more Smart Citations